TANGGUNG JAWAB DIREKSI DALAM PERSEROAN TERBATAS DI MAKASSAR (STUDI KASUS PUTUSAN NOMOR 11/Pdt. Sus-PHI/2019/PN.Mks): THE RESPONSIBILITY OF THE BOARD OF DIRECTORS IS LIMITED TO THE COMPANY IN MAKASSAR (DECISION NUMBER CASE STUDY 11/Pdt. Sus-PHI/2019/PN.Mks) - Okman, Arlan; A. Hasan, Yulia; M. Jafar, Juliati (Faculty Of Law Bosowa University, 2020)
The aim of this research is for determine the Directors responsibilities on Limited Liability Companies and find out what are the factors that caused the decision No. 11 / Pdt.Sus-PHI / 2019 / PN.Mks Niet Onkavelijke Veklaard. The research method used is a normative juridical research method, while the data collection uses qualitative methods. The results of this study indicate that the responsibility of the board of directors in the decision does not exist because the lawsuit in the case does not meet the formal requirements. However, if the claim is accepted and partially or fully granted, in carrying out the accountability, the board of directors in fulfilling the rights of employees' wages and severance pay acts on behalf of the PT and the responsibility is carried out based on the advice and decision of the judge. In addition, the factors of the decision No. 11 / Pdt.Sus-PHI / 2019 / PN.Mks Niet Ontvankelijke Verklaard are the failure to fulfill the formal requirements of the plaintiffs' lawsuit, where in this case only PT can become defendant as Persona In Judicio so that the lawsuit does not experience an error In Persona.